Raoultella ornithinolytica Isolation in Cloacal Microbiota of Tinamus solitarius: Preliminary Data - Marietto-Gonçalves,GA (2018)
ABSTRACT Raoultella ornithinolytica is a gram-negative aerobic bacterium belonging to Enterobacteriaceae family, an emerging pathogen that causes several pathogenic conditions in man, with little veterinary importance; however, its identification is underestimated by conventional laboratory techniques. The present study reports the identification of R. ornithinolytica in Tinamus solitaries, during a routine sanitary evaluation of aerobic enterobacteria in cloacal microbiota of birds belonging to the Güira Oga Center, Puerto Iguazu, Argentina. The sample was preliminary classified as Klebsiella spp.; however, after the use of the MALDI-TOF MS technique it was identified as R. ornithinolytica. The sample was submitted to an antimicrobial susceptibility test, where it showed a similar pattern profile as reported in the literature, with resistance to ampicillin and other β-lactam antibiotics. It is possible that Raoultella spp are more common in birds as it is reported. Therefore, review studies on bacteria collections of avian origin, as well as cases with confirmation of Klebsiella, should be deeply evaluated in laboratorial routine, mainly due to the pathogenic potential of R. ornithinolytica for Poultry, as well as for public health.